The Influence of Non-Cash Payments and Transaction Costs on Sharia Bank Customer Loyalty in Using M-Banking - Riyan Pradesyah; Munawaroh Munawaroh; Rizqy Fadhlina Putri (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Although m-banking offers convenience and efficiency, challenges appear when cost transaction rated too high by customers, which can reduce satisfaction them. In addition, the effectiveness feature payment non-cash in increase experience users also need evaluated. If the customer feels No satisfied with fees charged​ or available features, they​ Possible will switch to competitors. Research This aiming for analyze connection between second factor and its impact to loyalty Islamic bank customers. Research This aiming for analyze influence variable payment non-cash (X1), variable cost transaction (X2) against loyalty Islamic bank customers in using M-banking (Y). The research conducted using approach quantitative, with use application SmartPLS in data processing is carried out. Data obtained from results distribution questionnaire conducted​ to Respondent research, with method share google form to Respondent research. The results obtained that in a way partial There is influence significant variable X1 against Y is 52.39%, then variable X2 against Y has influence in a way significant by 19.80%. Then in a way simultaneous variable Payment Non-cash (X1), and Transaction Cost Variables (X2) can influence variable Loyalty of Sharia Bank Customers in Using M-Banking (Y) strong amounting to 77%, and the remaining 23 % is influenced variable others who don't under review in study.